(untitled) (International Journal of Innovative Research in Engineering & Management, 2021)
Of the many hardships at present faced globally, one is how to minimalize energy consumption by the consumption of fossil fuels due to the adverse social & environmental influences and worth unpredictability. Thus one of the approach is to make best use of the renewable sources of energy such as energy of sun in order to adhere to the global policies of clean energy development. Our country India has raised alarms in this issue. The combination of photovoltaic with thermal collector system was assumed in the direction of converting simultaneously the solar energy into electrical energy and heat energy as well. This whole process is done to encounter the low energy obtained when the two are used independently. Hence the concept of using the combination of thermal system with photovoltaic was to boost and optimization of PV panel efficiency. The construction of PV/T model uses water for conversion to thermal energy by the use of an appropriate technology.